2020
DOI: 10.1021/acs.jpcc.0c05244
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Complex Gas–Solid Interfaces with in Situ Spectroscopy: Oxygen Adsorption Behavior on Fe–N–C Catalysts

Abstract: Electrocatalysts for the oxygen reduction reaction (ORR) within polymer electrolyte membrane fuel cells (PEMFCs) based on iron, nitrogen, and carbon elements (Fe-N-C) have received significant research attention as they offer an inexpensive alternative to catalysts based on platinum-group metals (PGMs). While both the performance and the fundamental understanding of Fe-N-C catalysts have improved over the past decade, there remains a need to differentiate the relative activity of different active sites. Toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…On the weak OH* binding branch, step 1 (O 2 to OOH*) is the PDS. According to research on the interactions between Fe/N/C catalysts and oxygen under ultrahigh vacuum, the Fe/N/C catalysts strongly bind to oxygen. Therefore, we analyzed our Fe/N/C catalysts at the strong OH* binding branch of the “volcano.” This analysis revealed that step 4 (OH* to H 2 O) is the PDS.…”
Section: Resultsmentioning
confidence: 99%
“…On the weak OH* binding branch, step 1 (O 2 to OOH*) is the PDS. According to research on the interactions between Fe/N/C catalysts and oxygen under ultrahigh vacuum, the Fe/N/C catalysts strongly bind to oxygen. Therefore, we analyzed our Fe/N/C catalysts at the strong OH* binding branch of the “volcano.” This analysis revealed that step 4 (OH* to H 2 O) is the PDS.…”
Section: Resultsmentioning
confidence: 99%
“…The doublet D1 represents Fe 2+ coordinated by four pyrrolic N groups connected to a carbon support, and it is assigned to low-spin Fe 2+ –N 4 . The doublets D2 and D3 consist of ferrous intermediate-spin sites, and the main difference between the two doublets is their Fe local environments. ,,,,, The δ iso and Δ E Q values of D2 are close to those of FePc, while the values of D3 are similar to those of Fe porphyrins. , The singlet (Sing) represents superparamagnetic Fe, which has a smaller size than the Weiss domain; thus, it does not have a magnetic splitting value ( H 0 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various experimental characterization techniques have been used to investigate SAC structures and reactivity, especially in the case of iron. For example, the properties of Fe are characterized by 57 Fe Mössbauer spectroscopy, , X-ray absorption near-edge spectroscopy (XANES), and EXAFS. , High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) , is frequently utilized to confirm that metals are atomically dispersed in SACs. These spectroscopic analyses suggest that the support and primary coordination sphere are essential in determining catalytic reactivity, , consistent with conclusions drawn from DFT simulations. , Joint experimental characterization and computational studies have highlighted the roles of the support and primary coordination sphere for SACs in catalyzing HER, ORR, CO 2 RR, ,, and selective C–H bond oxidation. , …”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
“…Gu et al found that Fe­(III) does not get oxidized or reduced during the electrocatalytic reduction of CO 2 to CO, which contributed to the greater activity of Fe­(III) relative to conventional Fe­(II) sites . The 57 Fe Mössbauer spectroscopic studies necessary to assign the precise oxidation/spin states of the FeN x C y moiety remain challenging due to the distribution of sites that must be obtained from spectral fits. , Typically, SACs are modeled with plane-wave, semilocal DFT, in which the metal oxidation and spin states are either erroneously predicted or not precisely defined (i.e., due to fractional occupation of frontier states with smearing using semilocal DFT). To reveal the electronic structure of the metal and its relationship to the catalytic reactivity, efforts to understand SAC reactivity via molecular mimics have probed the effects of nitrogen type (e.g., pyridinic or pyrrolic), typically embedded in 14- or 16-membered macrocycles. ,, DFT modeling of finite size nanoflakes that represent the infinite system also help address the challenges in periodic systems …”
Section: Heterogeneous Catalystsmentioning
confidence: 99%